Legal Analysis of the Rights and Obligations of Teachers According to the Teachers and Lecturers Law - Romadhon; Mabruri Andatu; Muhamad Bintang; Muhammad Ramadhan; Jainudin Akmal Kamal (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study discusses the welfare of teachers in Indonesia, which is a major concern given their vital role in education. The background of this study focuses on the challenges faced by teachers, who often receive salaries below the minimum wage standard and do not have adequate legal protection when carrying out their duties. The methodology used is qualitative with descriptive data collection through case studies, and analysis of related literature. The results of the study indicate that 89% of teachers feel that their income is insufficient to meet their living needs, with many of them forced to look for side jobs. In addition, a survey by the Institute for Demographic and Poverty Studies (IDEAS) Research Institute and the Central Statistics Agency (BPS) revealed that teacher welfare, especially in remote areas, is very concerning and is an obstacle to improving the quality of education in Indonesia. This study emphasizes the need for serious attention from the government to improve the welfare of teachers so that they can carry out their educational duties more effectively.